Ornithodoros sonrai Soft Ticks and Associated Bacteria in Senegal - El Hadji Ibrahima Ndiaye; Adama Zan Diarra; Fatou Samba Diouf; Charles Bouganali; Lionel Almeras; Cheikh Sokhna; Georges Diatta; Philippe Parola (Pathogens, 2023)
The soft ticks, Ornithodoros sonrai, are known as vectors of the tick-borne relapsing fever caused by Borrelia spp. and have also been reported to carry other micro-organisms. The objective of this study was to collect and to identify O. sonrai ticks and to investigate the micro-organisms associated with them. In 2019, an investigation of burrows within human dwellings was conducted in 17 villages in the Niakhar area and in 15 villages in the Sine-Saloum area in the Fatick region of Senegal. Ticks collected from the burrows were identified morphologically and by matrix-assisted laser desorption ionization time-of-flight mass spectrometry (MALDI-TOF MS). Micro-organism screening was performed by bacteria-specific qPCR and some identifications were made by standard PCR and gene sequencing. O. sonrai ticks were found in 100% (17/17) of the villages surveyed in the Niakhar area and in 66% (10/15) of the villages in the Sine-Saloum area. A total of 1275 soft tick specimens were collected from small mammal burrows. The ticks collected were morphologically identified as O. sonrai. About 20% (259/1275) of the specimens were also submitted to MALDI-TOF MS for identification. Among the resulting MS profiles, 87% (139/159) and 95% (95/100) were considered good quality specimens, preserved in alcohol and silica gel, respectively. All spectra of good quality were tested against our MALDI-TOF MS arthropod spectra database and identified as O. sonrai species, corroborating the morphological classification. The carriage of four micro-organisms was detected in the ticks with a high prevalence of Bartonella spp., Anaplasmataceae, and Borrelia spp. of 35, 28, and 26%, respectively, and low carriage of Coxiella burnetii (2%). This study highlights the level of tick infestation in domestic burrows, the inventory of pathogens associated with the O. sonrai tick, and the concern about the potential risk of tick involvement in the transmission of these pathogens in Senegal.